Moisture Dependent Properties of Onion Neck and Leaf for Different Varieties of Harvested Onion Bulbs - Karate, Mayur; Bakane, Pramod; Kalbande, Surendra; Gupta, Suchita; Sonkamble, Arvind; Patil, Bhagyashree (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during December, 2024–May, 2025 for period of six month, at Department Agricultural Process Engineering, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola, Maharashtra, India to determine the moisture dependent properties of harvested onion neck and leaves for four different varieties. The four important varieties of onion were selected for study such as Nashik red, Bhima raj, Red china and Bhima super. The properties such as diameter of onion neck, moisture content of onion neck, force required to cut onion neck, tallest length of leaf and number of leaves were studied for selected variety in two categories i.e. freshly harvested and cured onions. The diameter of onion neck for all studied varieties were range from 11.37±1.53 mm–17.68±1.70 mm for freshly harvested and 7.37±1.53 mm–10.94±1.40 mm for cured onions. Moisture content of onion neck for all studied varieties ranged from 68.35±5.37%–77.55±2.89% for freshly harvested and 5.37±0.64%–6.01±1.07% for cured onions. The force required to cut onion neck for all studied varieties ranged from 108.27±45.83 N–170.84±22.03 N for freshly harvested and 74.36±25.25 N–171.90±78.58 N for cured onions. The tallest length of leaves for all studied varieties ranged from 386.78±47.93 mm–598.78±48.48 mm for freshly harvested and 186.64±38.83 mm–386.78±48.48 mm for cured onions. Number of leaves for all studied varieties ranged from 7.14±1.18–10.20±1.76 for freshly harvested and 3.48±1.55–6.68±1.70 for cured onions.